Household Waste Management towards a New Normal Era (Study at Suzuki Residents, Watutumou III Village, Kalawat District) - Ika Saputri Wulandari; Koderi Koderi; Soemarno Soemarno (Indonesian Journal of Environmental Management and Sustainability, 2021)
This research was conducted to (1) analyze the household waste management system, and (2) develop a strategy for household waste management in Suzuki Resident, Watutumou III Village, Kalawat District, getting in the era of "New Normal". This research uses quantitative methods with SWOT and AHP ((Analytical Hierarchy Process) techniques. The results show that the Waste Management system has Strength, such as the efforts to apply the 3R concept (Reduce, Reuse, and Recycle), waste management fees, and improvement, facilities and infrastructure, strengthening public understanding, support from local government and APBD (Local Government Budget) of North Minahasa Regency. The waste management system has several weaknesses, such as (1) lack of facilities and infrastructure for trash bins, the absence of 3R Landfill in residential areas, and limited human resource capacity toward waste management Opportunities which is faced by the waste management system including support for provincial government policies, facilitating the marketing of waste management products that are economically valuable. Threats which are faced are the increasing volume of waste, not optimal waste management and sorting, people behavior of littering. Based on these conditions, the priority of the Household Waste Management Strategy is to improve facilities and infrastructure to support waste management. The current strategy for developing a household waste management system is in quadrant IV that is diversifying the use of force and creating more opportunities. Strategic steps in managing household waste in Suzuki Resident, Watutumou III Village, Kalawat District, getting in the era of "New Normal, are improving existing facilities and infrastructure and adding to those that do not exist, optimizing waste retribution to support waste management costs, gathering support from stakeholders who related, strengthening public understanding of household waste management, and promoting efforts to apply the 3R concept in household waste management.